Electromagnetic hyperthermia on porous model of hepatic cancerous tissue. (16th July 2019) - Shamekhi, Leila; Sayehvand, Habib‐Olah; Karami, Hamidreza
Abstract: Because the effectiveness of interstitial hyperthermia is related to the temperature distribution achieved during the process, accurate understanding of energy transport within biological organs is necessary. This strongly depends on the complexity of the extended model. Herein, the coupled nonlinear set of transient equations for electromagnetic, momentum, and energy has been extended under two layered porous medium approximation. Maximum temperature value as well as its position has been traced in time by applying local thermal non‐equilibrium (LTNE). The boundary between cancerous and normal tissue has continuously been respected by different properties. The extended model is solved by a new computational approach. The results lead to a special slow and continuous moving antenna to achieve more effective cancerous cell death via normal cell safety.